2023
DOI: 10.1038/s41598-023-27712-2
|View full text |Cite
|
Sign up to set email alerts
|

A preclinical study comparing single- and double-root 3D-printed Ti–6Al–4V implants

Abstract: Recently, double-root implants have been investigated using 3D-printed technology. Here, we investigated damping capacity, microcomputed tomographic (micro-CT) and histological analyses of double-root 3D-printed implants compared with single-root 3D printed implants. Single- and double-root 3D-printed implants were fabricated and placed at both sides of mandibular third and fourth premolars in four beagle dogs. The damping capacity was measured, and periapical X-rays were taken every 2 weeks for 12 weeks. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Previously, our group established a digital workflow for the fabrication of double-root 3DIs that were designed in the shape of lattice- and solid-type roots, and found that the macrodesign of the implants may affect the secondary stability in vivo 15 . Furthermore, another study performed by our group comparing single and double-root 3DIs showed comparable implant stability and peri-implant bone remodeling, whereas higher marginal bone loss was observed in the furcation areas of double-root 3DIs 18 . However, there have been few related studies that fundamentally compared the in vivo clinical outcomes of 3DIs and CIs.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Previously, our group established a digital workflow for the fabrication of double-root 3DIs that were designed in the shape of lattice- and solid-type roots, and found that the macrodesign of the implants may affect the secondary stability in vivo 15 . Furthermore, another study performed by our group comparing single and double-root 3DIs showed comparable implant stability and peri-implant bone remodeling, whereas higher marginal bone loss was observed in the furcation areas of double-root 3DIs 18 . However, there have been few related studies that fundamentally compared the in vivo clinical outcomes of 3DIs and CIs.…”
Section: Introductionmentioning
confidence: 70%
“…Numerous studies of 3DIs have shown favorable clinical outcomes in vivo and have indicated a demand for further investigations into the actual implementation of 3DIs 15 18 . Previously, our group established a digital workflow for the fabrication of double-root 3DIs that were designed in the shape of lattice- and solid-type roots, and found that the macrodesign of the implants may affect the secondary stability in vivo 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Block biopsies including the experimental sites were obtained 6 weeks after the first surgery. Prior to histological preparation, micro-computed tomography (micro-CT) data of the samples were obtained, using the same conditions as in a previous study (13.3-μm resolution, 60 kV energy, and 167 μA intensity using 0.5-mm aluminum filter) 27 . The scanned images were reconstructed using software (DataViewer 1.5.2.4 64-bit version, Bruker microCT, Skyscan, Kontich, Belgium) and the data were analyzed with CTAn software (Bruker-CT, Kontich, Belgium).…”
Section: Methodsmentioning
confidence: 99%
“…The scanned images were reconstructed using software (DataViewer 1.5.2.4 64-bit version, Bruker microCT, Skyscan, Kontich, Belgium) and the data were analyzed with CTAn software (Bruker-CT, Kontich, Belgium). In accordance with previous studies 27 , 28 , 8-bit grayscale values ranging from 30 to 80 was set to identify bone tissue. Bone volume/tissue volume (BV/TV), bone surface/bone volume (BS/BV), the trabecular bone pattern factor (Tb.Pf), and structure model index (SMI) values within the VOI were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Zhong et al [122], double-root 3D tomography, micro-computed tomography (micro-CT), and histological analysis of a 3D printed implant were conducted. It was found that the stability and bone remodeling around the fixation of the 3D-printed double-root implant were comparable.…”
Section: Different Structures Of the Tooth Rootmentioning
confidence: 99%